Low Cost Health Monitoring Sytem Based on Internet Of Things Using Email Notification - I Dewa Gede Hari Wisana; Bedjo Utomo; Farid Amrinsani; Era Purwanto (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2021)
Monitoring activities are needed if there are symptoms of a disease that require quick action so that the patient's condition does not get worse, for that we need a system that can notify doctors so they can take action. The patient monitoring system in hospitals is generally still carried out conventionally, among others, nurses or doctors come to the patient's room to check on the progress of the patient's condition, this will be a problem, if the number of medical personnel and facilities is insufficient to monitor. Patients who need special attention for patient care, such as monitoring the patient's breathing rate. The use of the internet of things (IOT), as a device that can work without the help of people, can perform tasks and provide easier and real time data, so that they can access output directly. The purpose of this research is to design an inexpensive health monitoring tool based on the Internet of Things (Respiration Parameters) using a piezoelectric sensor and an ESP32 Wi-Fi module. From the results of the module design taken from 10 respondents, obtained that the average measurement high accuracy (17.76 + 0.61) and the average level of stability of the design has a magnitude of 0.4 so that it can be concluded that using a piezoelectric sensor in this series can obtain good accuracy. This the design can be used to monitor a person's respiration in real-time